PENDIDIKAN KARAKTER DAN IMPLEMENTASI DALAM PEMBELAJARAN MATEMATIKA - Arifin, Sujinal (Al 'Ilmi : Jurnal Pendidikan MIPA, 2012)
National education aims to develop the potential of students to become a faithful and pious human bevig to God the Almigty, to have noble character, health, knowledge, skills, creativity, independence, and become demotratic and accountable durigns. The formulation of national education goals is fundamental in the development of the nation’s character In a more narrow context such as mathematical context, the character is more emphasized on attitude and personally and also manners such as being critics, native, logica1 and flexible, persistent, precise and accurate besides, the other 18 values and characters that have been raised by Puskur (2011). The purpose of this paper writing is to describe the character values existed and can be developed in the learning of mathematics, as well as to describe the implementation of character education in learning mathematics. From this discussion it can be conchided that in the learning of mathematics actually contains the values of character, namely consistency, compliance, discipline, balance, creative, and innovative.